ANÁLISE COMPARATIVA DE RESULTADOS ECONÔMICOS: UM ESTUDO DE CASO NA PÓS-GRADUAÇÃO LATO SENSU DO CENTRO UNIVERSITÁRIO UNIVATES - Claus Haetinger (Universidade Federal de Santa Catarina, 2015)
Analysis of results have been important tools to decision support. This article analyzes thefinancial results and other indicators arising from Univates Graduate (lato sensu) curses from2008 till 2012, based on four different budgetary structures used during this period.Specifically, there are analyzed: the number of finished courses,the number of students, thedirect economic margin, the economical final result indicator on wage income, and thesharing classes in hours. The main goal has been to improve the economic and financialmanagement sector with a model that seeks to increasethe number of courses, the economicalresults of them, and also the number of students attended by these programs.